Enhanced isolation of SARS-CoV-2 by TMPRSS2- expressing cells - Matsuyama, Shutoku; Nao, Naganori; Shirato, Kazuya; Kawase, Miyuki; Saito, Shinji; Takayama, Ikuyo; Nagata, Noriyo; Sekizuka, Tsuyoshi; Katoh, Hiroshi; Kato, Fumihiro; Sakata, Masafumi; Tahara, Maino; et al. (Proceedings of the National Academy of Sciences - PNAS, 2020)
A novel betacoronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which caused a large respiratory outbreak in Wuhan, China in December 2019, is currently spreading across many countries globally. Here, we show that a TMPRSS2- expressing VeroE6 cell line is highly susceptible to SARS-CoV-2 infection, making it useful for isolating and propagating SARS-CoV-2. Our results reveal that, in common with SARS- and Middle East respiratory syndrome-CoV, SARS-CoV-2 infection is enhanced by TMPRSS2.